THE EFFECT OF USING DRILL METHOD TOWARD WRITING DESCRIPTIVE TEXT (A Study at the Seventh Grade Students of SMP Negeri 2 Padangsidimpuan) - JULIANA HARAHAP, S.Pd. (Jurnal Sinar Edukasi, 2020)
The objectives of this study is to find out is there a significant effect of using drill method toward writing descriptive text at the seventh grade students of SMP Negeri 2 Padangsidimpuan. This research is made by using experimental method. The purpose is to know the effect of drill method in writing descriptive text. Thus, the data in this research belongs to the writing descriptive text. In this research, the Seventh Grade Students of SMP Negeri 2 Padangsidimpuan have position as population with 180 students. Therefore, sample in this research is taken by using random sampling or 45 students. Furthermore, the writer uses test as the instrument to collect the data in which the test divided to pre-test and post-test. The writer uses descriptive and statistic analysis to analyze the data. Based on the descriptive analyzed, the writer shows that the average scores which got by students in X variable is 70.11 in which this score categorized to the good category. Meanwhile, the average scores which got by students in Y variable is 66.22 in which this score categorized to the enough category. Furthermore, statistic analysis shows that